Sustainability and carbon neutralization trends in microalgae bioenergy production from wastewater treatment: A review - Thanigaivel, Sundaram; Vickram, Sundaram; Manikandan, Sivasubramanian; Deena, Santhana Raj; Subbaiya, Ramasamy; Karmegam, Natchimuthu; Govarthanan, Muthusamy; Kim, Woong (Bioresource technology, 2022)
[Display omitted] •Impact of algal biodiesel is determined by a global sensitivity analysis from wastewater.•Waste CO2 is used for photosynthesis by microalgae grown in wastewater.•Capacity of microalgae to repair CO2 was investigated and discussed in detail.•Economic scaling indicates that algal biodiesel production is profitable.•Technological and economic examination of biodiesel production by algae is offered. Reducing CO2 emissions using biomass is gaining popularity as an environmentally friendly strategy. Due to high growth rates, low production costs, and ability to withstand harsh conditions, microalgae have become quite popular. Microalgae may also undertake photosynthesis, converting CO2 and solar energy into sugar before becoming biomass, making them an excellent source of renewable and promising biofuels. CO2 sequestration and biofixation was utilized to compare the synthesis of biodiesel as a third-generation biofuel from various types of wastewater was also used as a source for the algal cultivation. This review article focuses on recent developments, research discoveries in the field of microalgal CO2 capture modification and the optimization of conversion efficiency. This review is intended to serve as a helpful and reference for the use of wastewater treatment with microalgae to collect CO2. The overarching objective of this study is to assist wastewater treatment systems in achieving carbon neutrality.